PENGARUH PENDEKATAN CONCRETE PICTORIAL ABSTRACT (CPA) BERBANTUAN MEDIA PUZZLE TERHADAP PENINGKATAN PEMAHAMAN KONSEP MATEMATIS SISWA SD - Hafizhotul Millah, Nabila; Rahayu, Puji; Eka Putri, Hafiziani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Understanding mathematical concepts is an important foundation in learning mathematics because mathematics has concepts that are interconnected and continuous. However, in reality, there is still a low understanding of students' mathematical concepts in learning mathematics. The purpose of this study was to determine the increase in understanding of mathematical concepts of students who received learning with the CPA approach assisted by puzzle media with students who received learning with conventional. The research method used in this study is a quasi-experiment with a non-equivalent control group design on mathematics learning with the subject matter of simple fractions in class III elementary school with a total sample of 25 students from the experimental class and 25 students from the control class. The treatment of the CPA approach assisted by puzzle media was given to the experimental class while the control class was treated with the STAD type cooperative learning model. The mathematical concept understanding test instrument was used to obtain data before and after learning. The results showed that the increase in understanding of mathematical concepts of students who learned through the CPA approach assisted by puzzle media was better than students who used conventional learning and there was an effect of 65.7% of the application of the CPA approach assisted by puzzle media on students' understanding of mathematical concepts. Thus, the CPA approach with the help of puzzle media can be used as an alternative to mathematics learning that can help students understand mathematical concepts, especially in class III with the subject matter of simple fractions.